Paroxysmal and non-paroxysmal dystonia in 3 patients with biallelic ECHS1 variants: expanding the neurological spectrum and therapeutic approaches - Illsinger, Sabine; Korenke, Christoph; Boesch, Sylvia; Nocker, Michael; Karall, Daniela; Nuoffer, Jean M.; Laugwitz, Lucia; Mayr, Johannes A.; Scholl-Bürgi, Sabine; Freisinger, Peter; Kowald, Tobias; Kölker, Stefan; et al. (European journal of medical genetics, 2020)
Background - ECHS1 encodes the mitochondrial short chain enoyl CoA hydratase 1 (SCEH). Biallelic ECHS1 variants have been associated with Leigh-like presentations and milder phenotypes with paroxysmal exercise-induced dystonia. - Patients/methods - We used exome sequencing to investigate molecular bases of paroxysmal and non-paroxysmal dystonia in three patients and performed functional studies in fibroblasts. Disease presentation and response upon dietary interventions were documented. - Results - We identified compound heterozygous ECHS1 missense variants in all individuals; all of them harbouring an c.518C > T (p.Ala173Val) variant. SCEH activity was impaired in patients’ fibroblasts, respiratory chain-, and pyruvate-dehydrogenase-complex activities were normal in one individual. Patient 1 presented from the age of 2.5 years on with paroxysmal opisthotonic posturing. Patient 2 had a first metabolic crisis at the age 20 months developing recurrent exercise-induced dystonic episodes. Disease history of patient 3 was unremarkable for neurological findings until he first presented at the age of 20 years with persistent dystonia. Ketogenic diet had beneficial effects in patient 1. Neither ketogenic nor low protein diets led to milder symptoms in patient 2. Patient 3 benefits from low protein diet with improvement of his torticollis. - Conclusions - In line with literature, our findings corroborate that the pathogenic ECHS1 variant c.518C > T (p.Ala173Val) is associated with milder phenotypes characterized by paroxysmal and non-paroxysmal dystonia. Because of the potentially treatable defect, especially in milder affected patients, it is important to consider SCEH deficiency not only in patients with Leigh-like syndrome but also in patients with paroxysmal dystonia and normal neurological findings between episodes.
Gesehen am 07.12.2020